2012
DOI: 10.4314/sajas.v42i1.1
|View full text |Cite
|
Sign up to set email alerts
|

Comparison of the milk composition of free-ranging indigenous African cattle breeds

Abstract: The milk composition of free-ranging indigenous African cattle breeds was analysed. These breeds were chosen because they have not been bred specifically for milk production and might be considered the closest to a "natural" or "wild type" of the Bos species. It was found that the nutrient composition of the milk of these cattle, in particular the dry matter, is as low as that of European beef breeds. The content of whey proteins and NPN is also lower than that of dairy breeds. Statistically significant differ… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

6
33
2

Year Published

2014
2014
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 24 publications
(41 citation statements)
references
References 43 publications
6
33
2
Order By: Relevance
“…Similar observation was reported for mountainous farms in the Czech Republic (Frelich et al 2009) but a reverse trend was observed when milk from the Black-White breed of cattle was analysed . Regardless of season, the content of butyric acid in this study was higher compared with African breeds studied by Myburgh et al (2012). The average content of anticancerogenic C4:0 in our study (4.20 g·100 g -1 FA) was also by about 25 % higher than in milk from the mountainous region in Switzerland (3.38 g·100 g -1 FA) (Collomb et al 2008).…”
Section: Resultscontrasting
confidence: 57%
See 2 more Smart Citations
“…Similar observation was reported for mountainous farms in the Czech Republic (Frelich et al 2009) but a reverse trend was observed when milk from the Black-White breed of cattle was analysed . Regardless of season, the content of butyric acid in this study was higher compared with African breeds studied by Myburgh et al (2012). The average content of anticancerogenic C4:0 in our study (4.20 g·100 g -1 FA) was also by about 25 % higher than in milk from the mountainous region in Switzerland (3.38 g·100 g -1 FA) (Collomb et al 2008).…”
Section: Resultscontrasting
confidence: 57%
“…That level was nearly twice higher compared with the data of Grega et al (2005) reported for the Red-White breed of cows fed similarly as ours experimental PRW herd. Also, fat from milk of indigenous breeds of African and Malaysian dairy cattle contained lower levels of PUFAs -2.61 g·100 g -1 and 2.12 g·100 g -1 , respectively (Myburgh et al 2012, Yassir et al 2010. Higher content of that FA group in milk from Czech Pied breed (6.67 g·100 g -1 ) was probably due to feeding cows maize and alfalfa silages with addition of barley, wheat and soy (Pešek et al 2005).…”
Section: Resultsmentioning
confidence: 93%
See 1 more Smart Citation
“…To date, no previous data on the fatty acid composition of milk fat of Nguni, Boer and non-descript goat breeds is available in the literature. Conversely, several studies have reported the effect of breeds on milk fatty acid profile in other livestock such as ewes (Talpur et al 2009) and cows (Myburgh et al 2012). However, most studies have focused on evaluating the effect of diet on fatty acid profile of milk fat in livestock (Bouattour et al 2008;Tyagi et al 2010).…”
Section: Discussionmentioning
confidence: 99%
“…Analytic inaccuracy is of particular concern for milks that are very different in composition from the milks of dairy animals, especially marine mammals. The Comparison of analytical and predictive methods for water, protein, fat, sugar, and gross energy in marine mammal milk O. T. Oftedal ,* 1 R. Eisert ,* † and G. K. Barrell ‡ milks of marine mammals are not only much higher in fat (typically 15-40% in cetaceans and 25-60% in pinnipeds) than cow milk (2-5%, depending on breed; e.g., Myburgh et al 2012), but contain much greater diversity and abundance of long-chain PUFA and, in some taxa, more complex oligosaccharides than do the milks of dairy animals (Iverson and Oftedal, 1995;Urashima et al, 2011;Oftedal, 2011). In some taxa, NPN may represent a large portion of total N, FFA may be present if samples are handled inappropriately, and instability of thawed milks may lead to substantial sample-to-sample heterogeneity Ochoa-Acuna et al, 1999).…”
Section: Introductionmentioning
confidence: 99%